Tips for planning formal farm surveys in developing countries: IITA research guide, No. 31 - Horton, D. (1997)
Formal surveys are powerful tools in gathering information from farmers I order to arrive at wise decisions in the implementation of agriculture development projects. However, formal surveys must be used with common sense and a dedication to clear focus by gathering useful data. The temptation to construct long, awkward questionnaires involving interesting but essentially irrelevant questions must be avoided. Above all, however, we should demand that the survey yield information that will help to solve farmers' problem.